ANALISIS KESALAHAN SISWA KELAS VII SMP NEGERI 7 PALU DALAM MENYELESAIKAN SOAL GARIS DAN SUDUT BERDASARKAN JENIS KELAMIN: Analysis Of Errors Of Class VII Students Of SMP Negeri 7 Palu In Solving Line And Angle Questions Based On Gender - Juliyanti; Sugita, Gandung; Anggraini; Alfisyahra (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This research aims to describe the types of errors made by class VII D students of SMP Negeri 7 Palu in solving line and angle problems based on gender. Data was obtained from the results of written assignments and interviews. The research subjects consisted of one male student (AA) and one female student (YS). The results of the research show that there are similarities and differences between male and female students in making written assignments number 1 and 2. Male and female students make the same mistakes in written assignment number 1. The similarities are: 1) Errors of not understanding the concept of the relationship between angles that are supplementary to each other, 2) the error of not understanding the concept of the relationship between the interior and exterior angles of a triangle, 3) the error of not solving the problem according to the instructions, 4) the error of not being coherent in the calculation steps, 5) the error of using arithmetic operation signs, 6) Error calculating the value of a calculation operation. Meanwhile, in written assignment number 2, there were differences in errors made by male and female students. The male students' mistakes were: 1) The male students were correct in doing the questions according to the instructions but not completely or comprehensively, 2) The male students were not careful and rushed in solving the questions. The female student's mistakes in written assignment number 2 were: 1) The female student was correct in choosing the formula but could not apply the formula, 2) The female student solved the problem not according to the procedure ordered. The similarity between male and female students in completing written assignment number 2 is that in the problem solving procedure they can group similar and dissimilar terms in the written assignment.